Effects of Frailty on Outcomes Following Surgery Among Patients With Hip Fractures: A Systematic Review and Meta-Analysis - Ma, Yan; Wang, Ansu; Lou, Yijiao; Peng, Daojuan; Jiang, Zhongyan; Xia, Tongxia (Frontiers in Medicine, 2022)
Background: Frailty is a syndrome of multisystem dysfunction in the elderly. The association between preoperative frailty and postoperative outcomes in patients with hip fractures is unclear. To address this issue, we performed a meta-analysis to determine the association of frailty with postoperative mortality, complications, and readmission in patients with hip fractures. Methods: We searched PubMed, Web of Science, Embase, and The Cochrane Library for cohort studies of frailty associated with postoperative adverse events in patients with hip fractures from inception to November 6, 2021. The Newcastle-Ottawa Scale was used to evaluate the quality of the included literature. Statistical analysis of meta-analysis was performed using Review Manager 5.3. Results: Twelve retrospective cohort studies and seven prospective cohort studies involving a total of 62132 patients met the inclusion criteria for this meta-analysis. Compared with non-frail patients, the pooled results showed that frailty was associated with patient in-hospital mortality (relative risk [RR] = 2.93; 95% confidence intervals [CI]: 2.56-3.34), 30-day mortality (RR = 2.85, 95%CI: 1.67-4.85) and total complications (RR = 1.79, 95%CI: 1.50-2.15). Subgroup analysis showed that the type of study design and frailty assessment tool had no significant effect on the results. Sensitivity analysis showed that the polled results of frailty predicted one-year mortality and 30-day readmission was unstable. Conclusions: In this meta-analysis, we found that preoperative frailty may be associated with postoperative adverse events in patients with hip fracture, including in-hospital mortality, 30-day mortality, and postoperative complications.